Phytochemical and Biological Activity of Cucurbita Seed Extract - Ethiraj, Sumathi; Balasundaram, Janarthanam (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2016)
The present study was performed to investigate the phytochemical screening, total phenol, tannin content, antioxidant and antibacterial activity from seed extracts of Cucurbita pepo and Cucurbita maxima (Tindivanam). The phytochemical analysis revealed the presence of active ingredients such as steroids, cardioglycosides, phenols, terpenoids, alkaloids and tannins in the seed extract of Cucurbita pepo followed by Cucurbita maxima. Gallic acid (GA), Tannic acid (TA) and Butylated Hydroxy Toluene (BHT) were taken as standard in case of total phenol, tannin and antioxidant activity respectively. Total phenol and tannin content were quantitatively estimated which recorded maximum in Cucurbita pepo (8.37±0.2 mg Gallic Acid Equivalents (GAE)/g and 20.47 ± 0.37 mg Tannic Acid Equivalents (TAE)/g). The seed extracts were evaluated for antioxidant activities by DPPH (1, 1– Diphenyl -2- picryl - hydrazyl) radical scavenging assay. Among the two species with different solvents used, maximum antioxidant activity was found in the acetone seed extract (84.27±0.19%) of Cucurbita pepo followed by Cucurbita maxima (67.83 ± 0.37%). Different concentrations of acetone seed extracts were tested for the anti-bacterial activity against Bacillus subtilis, Bacillus cereus, Staphylococcus aureus, Pseudomonas aeruginosa and Escherichia coli using the agar disc diffusion technique. The acetone seed extracts of Cucurbita pepo had superior level of antimicrobial activity. The powerful antibacterial effect is attributed to the greater amount of tannins compound in the acetone seed extracts of Cucurbita pepo.